(x-1)*(x+3)=0

Simple and best practice solution for (x-1)*(x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-1)*(x+3)=0 equation:


Simplifying
(x + -1)(x + 3) = 0

Reorder the terms:
(-1 + x)(x + 3) = 0

Reorder the terms:
(-1 + x)(3 + x) = 0

Multiply (-1 + x) * (3 + x)
(-1(3 + x) + x(3 + x)) = 0
((3 * -1 + x * -1) + x(3 + x)) = 0
((-3 + -1x) + x(3 + x)) = 0
(-3 + -1x + (3 * x + x * x)) = 0
(-3 + -1x + (3x + x2)) = 0

Combine like terms: -1x + 3x = 2x
(-3 + 2x + x2) = 0

Solving
-3 + 2x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -1x)(1 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {-3, 1}

See similar equations:

| -108/18= | | 56.52=2*3.14*r | | ln(6x-8)=1.3 | | 7a+3=66 | | 10+10x=109+1x | | 6(n+7)=60 | | ((-18x^(0)a^(3))/(6(x^(-2))(x^(3)a^(2))))^(2) | | =80 | | 9(-3+p)=-54 | | 9x+8x-3x-5=23 | | 5(b-5)=70 | | 2+7x=56+1x | | 6=-8y+3(y-3) | | 0.5x+0.2x=0.4x+5 | | 179=5d/11 | | 7y+3y-10=180 | | -6+8a+4x-2+2a=10a+4 | | 2x-2x-1-1=0 | | 2x+4-6x+2=4x+7.9 | | 2(3r+1)+2r= | | 7-u=12 | | 4y-3+x-6=6y-9 | | 12w+30=20 | | -60=-6(x-3) | | x+(x+5)+3x+(3x-3)=114 | | X^2-94x-7200=0 | | X^2-94x-720=0 | | 41.9x^2-45.9x+11.48=0 | | 6x+3=10+4x | | C=24+15d | | 20/35=21/x | | 2x/6=2 |

Equations solver categories